Road Traffic Accident and its Characteristics in Kathmandu Valley - Ling Huang; Krishna P Adhikary; Bishnu P Choulagai; Nanping Wang; Amod K Poudyal; Sharad R Onta (Journal of Nepal Medical Association, 2016)
Introduction: Road traffic accident is alarming in Nepal. The objective of this research is to find out the characteristics of RTA in central part of Nepal. Methods: A prospective descriptive study was taken from 1 August 2014 to 31 July 2015. Data were collected from postmortem department and nine hospitals in Kathmandu Valley. Inventory sheets with targeted variables for secondary sources were created. Results: A total of 3461 morbidity cases from hospitals and 265 mortality cases from postmortem department were included in this study. The ratio of male victim to female was 2.3:1. Around 75% of victims were between 15-49 years old. Pedestrians were the most vulnerable (33%) followed by riders of motorized 2-3 wheelers. Two wheeler motorized vehicles were most frequently (67.2%)involved in RTAs. More RTA occurred on daytime, Saturdays, July and November. Around half of the victims did not arrive in hospitals in one hour. The most common injury type was soft tissue injury (37.6%), followed by open wound (20.9%), fracture (18%) and traumatic brain injuries (12.7%). Conclusions: According to the characteristic of RTA found in this study, following preventive measures are recommended Helmet was necessary for two wheeled backseat riders. Road safety education towards age group of 15-49 was compulsory. Precaution should neither be omitted regarding road safety on weekends, holidays, nor in rainy and festival season. Future studies could be focused on estimation of burden of disease caused by RTA and its determinants in Nepal. Keywords: injury; Nepal; road traffic accident; road safety. | PubMed